Key process mineralogy parameters for rare earth fluorcarbonate-bearing carbonatite deposits: The example of Songwe Hill, Malawi. (1st December 2020) - Al-Ali, Safaa; Wall, Frances; Fitzpatrick, Robert; Broom-Fendley, Sam; Rollinson, Gavyn; Brady, Aoife E.; Pickles, Jonathan R.; Williams, Adam; Dawes, Will
Highlights: Process mineralogy is fundamental prior to conducting mineral processing tests. The Songwe Hill carbonatite deposit consists of valuable apatite and synchysite-(Ce). Well liberated apatite hosts the majority of heavy rare earth elements (HREE). Poorly-liberated synchysite-(Ce) hosts light rare earth elements (LREE) and some HREE. Fine grinding, magnetic separation and froth flotation is applicable processing flowsheet. Abstract: Rare earth element (REE)-bearing carbonatite deposits commonly contain a wide range of different REE- and REE-bearing minerals associated with various gangue matrices. In order to select the most-suitable mineral processing technique for these deposits, it is essential to identify and quantify the minerals of interest, including their liberation, associations and grain size distribution, along with whole rock compositions. These data are also vital for ore feed optimisation and metallurgical troubleshooting during and after designing a mineral processing flowsheet. This paper summarises the key mineralogical parameters needed before conducting metallurgical beneficiation tests, using the Songwe Hill carbonatite deposit as an example. This REE ore deposit consists of poorly-liberated synchysite-(Ce), which hosts the light rare earth elements including Nd plus some heavy rare earths and well-liberated apatite, which hosts 50% of Gd, 63% of Dy and 71% of Y (heavy rare earth elements) in the deposit. For all REE heavier than Gd, apatite is the most important REE host, however, for the two REE where data are available in both synchysite-(Ce) and apatite (Dy and Y), synchysite-(Ce) still accommodates >25% of the whole-rock HREE content. Both of these ore minerals are associated with ankerite, calcite, and to a lesser extent with iron oxides/carbonates, K-feldspar, strontianite and baryte. According to the quantitative mineralogical data, the possibility of using gravity separation, magnetic separation, froth flotation and leaching to process Songwe Hill carbonatite ore is discussed and a potential beneficiation flowsheet is presented.